Toleransi Beragama Di Lingkungan Sekolah Dasar: Jumat Bersih, Praktik dan Koeksistensi - Khamala, Khamidatul; Andriyani, Santi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article examines the level of religious tolerance at Tanjung State Elementary School 2, located in Pakis Sub-district, Jepara Regency. The main focus is on the Clean Friday program as a practice that influences and reflects interfaith coexistence. This study aims to analyze how the implementation of the Clean Friday program plays a role in building religious tolerance in the school environment. The research method used is qualitative using interviews, observation, and document analysis. The main respondents included students, Islamic religious education teachers, and school staff. Data analysis was conducted with a descriptive approach. The results showed that the Clean Friday program has made a positive contribution in improving the understanding and practice of religious tolerance at Tanjung State Elementary School. The program also reflects interfaith coexistence, where students from different religious backgrounds can interact harmoniously during its implementation. This research provides valuable insights into efforts to build religious tolerance at the primary level, focusing on concrete practices such as the Clean Friday program.